2017
DOI: 10.1121/1.4978363
|View full text |Cite
|
Sign up to set email alerts
|

A finite element study on the cause of vocal fold vertical stiffness variation

Abstract: A finite element method based numerical indentation technique was used to quantify the effect of the material stiffness variation and the subglottal convergence angle of the vocal fold on the vertical stiffness difference of the medial surface. It was found that the vertical stiffness difference increased with the increasing subglottal angle, and it tended to saturate beyond a subglottal angle of about 50°. The material stiffness variation could be as important as the subglottal angle depending on the actual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The details about the numerical indentation method can be found in Ref. [34]. To obtain the distribution of the stiffness, the medial surface of the vocal fold was evenly divided into 21 sections with seven sections in the longitudinal direction and three sections in the vertical direction (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The details about the numerical indentation method can be found in Ref. [34]. To obtain the distribution of the stiffness, the medial surface of the vocal fold was evenly divided into 21 sections with seven sections in the longitudinal direction and three sections in the vertical direction (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Let P be the pressure load, A be the loading area, and Dx be the maximum deformation, the stiffness k was computed as k¼PA/Dx. The details of this method are referred to Geng et al 47 In the current study, P ¼ 4 kPa and A ¼ 1 mm 2 . The constant pressure loading was applied to create a loading condition comparable to that during flowstructure interactions.…”
Section: A Effect On Vocal Fold Stiffnessmentioning
confidence: 99%
“…It was caused by two factors. The first is related to the asymmetric geometry of the vocal fold from inferior to superior and that the extra subglottal part provided more resistance to the loading according to Geng et al 47 The second is related to the fact that some parts of the superior measurement area only had the resistance from the cover layer below it while all the inferior measurement area had the resistance from the cover, ligament, and body layers.…”
Section: A Effect On Vocal Fold Stiffnessmentioning
confidence: 99%
“…The Psg value, which signifies the lung pressure or the vocal effort, imposes the extent of the lateral force that acts on the medial wall to displace the fold. The reaction to that force varies along the glottal height due to the inferior-superior tissue stiffness gradient [ 13 15 ]. In previous studies using an indentation test to characterize this gradient showed that the superior edge was about as stiff as the inferior edge at small displacement values (i.e., low strains).…”
Section: Introductionmentioning
confidence: 99%